1994
DOI: 10.1111/j.1749-6632.1994.tb56858.x
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Sulphate (DHEAS) in the Oldest Old, Aged 85 and Overa

Abstract: Dehydroepiandrosterone (DHEA) and its sulphonated metabolite DHEAS are the major secretory products of the human adrenal gland. Despite the abundancy of these steroids in the circulation the precise function is uncertain. It has been postulated that they may be involved in the maturing and aging processes in man. An intriguing inverse relation has been described between DHEAS and cardiovascular mortality in men. In women from the same population this was not the case and in fact mortality due to cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 24 publications
3
25
0
2
Order By: Relevance
“…P values are given controlling for age: *, P Ͻ 0.05; **, P Ͻ 0.01; ***, P Ͻ 0.001. women after 65 years of age, even if the decrease with age continues to be significant in men but not in women, after correcting for health indicators. We are currently measuring DHEAS in the serum of Ϸ400 of the original 622 people reported here, and will then obtain a longitudinal picture of the DHEAS decrease with age, which may vary considerably according to the individuals (46). Results concerning functional dependence in our study go in the same direction as those previously observed in men and women taken together, such as in the Established Populations for the Epidemiologic Study of the Elderly study (47) and two other more limited studies (44,48).…”
Section: Discussionsupporting
confidence: 72%
“…P values are given controlling for age: *, P Ͻ 0.05; **, P Ͻ 0.01; ***, P Ͻ 0.001. women after 65 years of age, even if the decrease with age continues to be significant in men but not in women, after correcting for health indicators. We are currently measuring DHEAS in the serum of Ϸ400 of the original 622 people reported here, and will then obtain a longitudinal picture of the DHEAS decrease with age, which may vary considerably according to the individuals (46). Results concerning functional dependence in our study go in the same direction as those previously observed in men and women taken together, such as in the Established Populations for the Epidemiologic Study of the Elderly study (47) and two other more limited studies (44,48).…”
Section: Discussionsupporting
confidence: 72%
“…Although many studies find no relationship with various measures of cognitive function for either sex (Berr et al, 1996;Burkenhäger-Gillesse et al, 1994;Yaffe et al, 1998), three studies (one of which is longitudinal) report a link between DHEAS and cognitive function among men, but no difference among women (Mazat et al, 2001;Tilvis et al, 1999;Ravaglia et al, 2002). In contrast, Morrison et al (2000) report a positive correlation between DHEAS and cognitive impairment among women.…”
Section: Introductionmentioning
confidence: 72%
“…Ravaglia et al demonstrated that it can matter, because within the old male group at least, the level of DHEA correlated with their health, as measured on the ADL scale. On the other hand, DHEA levels are clearly reduced in the aged although the degree of reduction fails to correlate with health status as assessed by the strict SENIEUR protocol (595). A supplementation trial to assess the effects of DHEA on responses to tetanus and influenza vaccination in man did not yield as dramatic effects as seen in mice (596): there was a trend toward increased antibody titers to influenza but not tetanus, and even this failed to reach significance (596).…”
Section: Hormonesmentioning
confidence: 99%